Photosynthesis, heat, and structure: an evident hierarchy of environmental conditions driving wetland carbon assimilation - Eric Romero; Camilo Rey-Sanchez; Cynthia Gerlein-Safdi; Dennis D. Baldocchi; Philip Lee; Iryna Dronova (Remote Sensing of Environment, 2026)

Interannual Variability in Greenhouse Gas Emissions Challenges Post‐Restoration Net Sink Predictions in California Delta Wetlands - Kuno Kasak; Arman Ahmadi; Iryna Dronova; Ariane Arias‐Ortiz; Tianxin Wang; Alex C. Valach; Daphne Szutu; Joseph Verfaillie; Dennis D. Baldocchi (Global Change Biology, 2026)
Globally, wetlands can sequester and store large amounts of soil carbon over the long term due to high primary productivity and slow decomposition. Yet centuries of drainage for agriculture and development have turned many of these carbon sinks into greenhouse gas (GHG) sources. Restoring degraded wetlands, particularly in peat‐rich landscapes, is increasingly promoted as a nature‐based solution for climate change mitigation. However, the trajectory and timing of recovery remain uncertain, especially given the complex interplay among vegetation dynamics, hydrology, and GHG fluxes. In this study, we analyzed 44 site‐years of continuous eddy covariance measurements of carbon dioxide (CO 2 ) and methane (CH 4 ) fluxes from restored wetlands in California's Sacramento‐San Joaquin Delta. Our findings reveal substantial interannual variability in GHG exchange across sites, driven by differences in restoration design, water management, and vegetation establishment. While rapid vegetation growth, especially dense stands of macrophytes, can enhance CO 2 uptake, it often elevates CH 4 emissions and complicates predictions of when wetlands become net GHG sinks. Crucially, wetlands with delayed vegetation establishment due to high or inconsistent water levels (e.g., significant drawdown) remained persistent GHG sources, even years after restoration. Conversely, sites with tailored planting or natural and rapid recolonization exhibited earlier transitions to net sink status, including earlier shifts towards net negative radiative forcing since the restoration. The study highlights the importance of adaptive, site‐specific restoration strategies and long‐term monitoring to capture switchover dynamics from sources to sinks. As global investment in wetland restoration grows, our findings underscore the need to balance climate mitigation goals with ecological realities and the self‐designing processes of vegetation succession.

Methane fluxes in tidal marshes of the conterminous United States - Ariane Arias‐Ortiz; Jaxine Wolfe; Scott D. Bridgham; Sara Knox; Gavin McNicol; Brian A. Needelman; Julie Shahan; Ellen J. Stuart‐Haëntjens; Lisamarie Windham‐Myers; Patty Y. Oikawa; Dennis D. Baldocchi; Joshua S. Caplan; et al. (Global Change Biology, 2024)
Methane (CH 4 ) is a potent greenhouse gas (GHG) with atmospheric concentrations that have nearly tripled since pre‐industrial times. Wetlands account for a large share of global CH 4 emissions, yet the magnitude and factors controlling CH 4 fluxes in tidal wetlands remain uncertain. We synthesized CH 4 flux data from 100 chamber and 9 eddy covariance (EC) sites across tidal marshes in the conterminous United States to assess controlling factors and improve predictions of CH 4 emissions. This effort included creating an open‐source database of chamber‐based GHG fluxes ( https://doi.org/10.25573/serc.14227085 ). Annual fluxes across chamber and EC sites averaged 26 ± 53 g CH 4 m −2 year −1 , with a median of 3.9 g CH 4 m −2 year −1 , and only 25% of sites exceeding 18 g CH 4 m −2 year −1 . The highest fluxes were observed at fresh‐oligohaline sites with daily maximum temperature normals (MATmax) above 25.6°C. These were followed by frequently inundated low and mid‐fresh‐oligohaline marshes with MATmax ≤25.6°C, and mesohaline sites with MATmax >19°C. Quantile regressions of paired chamber CH 4 flux and porewater biogeochemistry revealed that the 90th percentile of fluxes fell below 5 ± 3 nmol m −2 s −1 at sulfate concentrations >4.7 ± 0.6 mM, porewater salinity >21 ± 2 psu, or surface water salinity >15 ± 3 psu. Across sites, salinity was the dominant predictor of annual CH 4 fluxes, while within sites, temperature, gross primary productivity (GPP), and tidal height controlled variability at diel and seasonal scales. At the diel scale, GPP preceded temperature in importance for predicting CH 4 flux changes, while the opposite was observed at the seasonal scale. Water levels influenced the timing and pathway of diel CH 4 fluxes, with pulsed releases of stored CH 4 at low to rising tide. This study provides data and methods to improve tidal marsh CH 4 emission estimates, support blue carbon assessments, and refine national and global GHG inventories.

Correction: On the Relationship Between Aquatic CO2 Concentration and Ecosystem Fluxes in Some of the World’s Key Wetland Types - Jessica L. Richardson; Ankur R. Desai; Jonathan Thom; Kim Lindgren; Hjalmar Laudon; Matthias Peichl; Mats Nilsson; Audrey Campeau; Järvi Järveoja; Peter Hawman; Deepak R. Mishra; Dontrece Smith; et al. (Wetlands, 2024)

On the Relationship Between Aquatic CO2 Concentration and Ecosystem Fluxes in Some of the World’s Key Wetland Types - Jessica L. Richardson; Ankur R. Desai; Jonathan Thom; Kim Lindgren; Hjalmar Laudon; Matthias Peichl; Mats Nilsson; Audrey Campeau; Järvi Järveoja; Peter Hawman; Deepak R. Mishra; Dontrece Smith; et al. (Wetlands, 2024)

Practical Guide to Measuring Wetland Carbon Pools and Fluxes - Sheel Bansal; Irena F. Creed; Brian A. Tangen; Scott D. Bridgham; Ankur R. Desai; Ken W. Krauss; Scott C. Neubauer; Gregory B. Noe; Donald O. Rosenberry; Carl Trettin; Kimberly P. Wickland; Scott T. Allen; et al. (Wetlands, 2023)
Wetlands cover a small portion of the world, but have disproportionate influence on global carbon (C) sequestration, carbon dioxide and methane emissions, and aquatic C fluxes. However, the underlying biogeochemical processes that affect wetland C pools and fluxes are complex and dynamic, making measurements of wetland C challenging. Over decades of research, many observational, experimental, and analytical approaches have been developed to understand and quantify pools and fluxes of wetland C. Sampling approaches range in their representation of wetland C from short to long timeframes and local to landscape spatial scales. This review summarizes common and cutting-edge methodological approaches for quantifying wetland C pools and fluxes. We first define each of the major C pools and fluxes and provide rationale for their importance to wetland C dynamics. For each approach, we clarify what component of wetland C is measured and its spatial and temporal representativeness and constraints. We describe practical considerations for each approach, such as where and when an approach is typically used, who can conduct the measurements (expertise, training requirements), and how approaches are conducted, including considerations on equipment complexity and costs. Finally, we review key covariates and ancillary measurements that enhance the interpretation of findings and facilitate model development. The protocols that we describe to measure soil, water, vegetation, and gases are also relevant for related disciplines such as ecology. Improved quality and consistency of data collection and reporting across studies will help reduce global uncertainties and develop management strategies to use wetlands as nature-based climate solutions.

A novel approach to partitioning evapotranspiration into evaporation and transpiration in flooded ecosystems - Elke Eichelmann; Mauricio C. Mantoani; Samuel D. Chamberlain; Kyle S. Hemes; Patricia Y. Oikawa; Daphne Szutu; Alex Valach; Joseph Verfaillie; Dennis D. Baldocchi (Global Change Biology, 2022)
Reliable partitioning of micrometeorologically measured evapotranspiration (ET) into evaporation ( E ) and transpiration ( T ) would greatly enhance our understanding of the water cycle and its response to climate change related shifts in local‐to‐regional climate conditions and rising global levels of vapor pressure deficit (VPD). While some methods on ET partitioning have been developed, their underlying assumptions make them difficult to apply more generally, especially in sites with large contributions of E . Here, we report a novel ET partitioning method using artificial neural networks (ANNs) in combination with a range of environmental input variables to predict daytime E from nighttime ET measurements. The study uses eddy covariance data from four restored wetlands in the Sacramento‐San Joaquin Delta, California, USA, as well as leaf‐level T data for validation. The four wetlands vary in their vegetation make‐up and structure, representing a range of ET conditions. The ANNs were built with increasing complexity by adding the input variable that resulted in the next highest average value of model testing R 2 across all sites. The order of variable inclusion (and importance) was: VPD > gap‐filled sensible heat flux ( H _gf) > air temperature ( T air ) > friction velocity ( u ∗ ) > other variables. The model using VPD, H _gf, T air , and u ∗ showed the best performance during validation with independent data and had a mean testing R 2 value of 0.853 (averaged across all sites, range from 0.728 to 0.910). In comparison to other methods, our ANN method generated T /ET partitioning results which were more consistent with CO 2 exchange data especially for more heterogeneous sites with large E contributions. Our method improves the understanding of T /ET partitioning. While it may be particularly suited to flooded ecosystems, it can also improve T /ET partitioning in other systems, increasing our knowledge of the global water cycle and ecosystem functioning.

Measurement of Fluxes Over Land: Capabilities, Origins, and Remaining Challenges - Bruce B. Hicks; Dennis D. Baldocchi (Boundary-Layer Meteorology, 2020)

Effect of Drought-Induced Salinization on Wetland Methane Emissions, Gross Ecosystem Productivity, and Their Interactions - Samuel D. Chamberlain; Kyle S. Hemes; Elke Eichelmann; Daphne J. Szutu; Joseph G. Verfaillie; Dennis D. Baldocchi (Ecosystems, 2020)

Where old meets new: An ecosystem study of methanogenesis in a reflooded agricultural peatland - Gavin McNicol; Sara H. Knox; Thomas P. Guilderson; Dennis D. Baldocchi; Whendee L. Silver (Global Change Biology, 2020)
Reflooding formerly drained peatlands has been proposed as a means to reduce losses of organic matter and sequester soil carbon for climate change mitigation, but a renewal of high methane emissions has been reported for these ecosystems, offsetting mitigation potential. Our ability to interpret observed methane fluxes in reflooded peatlands and make predictions about future flux trends is limited due to a lack of detailed studies of methanogenic processes. In this study we investigate methanogenesis in a reflooded agricultural peatland in the Sacramento Delta, California. We use the stable‐and radio‐carbon isotopic signatures of wetland sediment methane, ecosystem‐scale eddy covariance flux observations, and laboratory incubation experiments, to identify which carbon sources and methanogenic production pathways fuel methanogenesis and how these processes are affected by vegetation and seasonality. We found that the old peat contribution to annual methane emissions was large (~30%) compared to intact wetlands, indicating a biogeochemical legacy of drainage. However, fresh carbon and the acetoclastic pathway still accounted for the majority of methanogenesis throughout the year. Although temperature sensitivities for bulk peat methanogenesis were similar between open‐water ( Q 10 = 2.1) and vegetated ( Q 10 = 2.3) soils, methane production from both fresh and old carbon sources showed pronounced seasonality in vegetated zones. We conclude that high methane emissions in restored wetlands constitute a biogeochemical trade‐off with contemporary carbon uptake, given that methane efflux is fueled primarily by fresh carbon inputs.

How eddy covariance flux measurements have contributed to our understanding of Global Change Biology - Dennis D. Baldocchi (Global Change Biology, 2020)
A global network of long‐term carbon and water flux measurements has existed since the late 1990s. With its representative sampling of the terrestrial biosphere's climate and ecological spaces, this network is providing background information and direct measurements on how ecosystem metabolism responds to environmental and biological forcings and how they may be changing in a warmer world with more carbon dioxide. In this review, I explore how carbon and water fluxes of the world's ecosystem are responding to a suite of covarying environmental factors, like sunlight, temperature, soil moisture, and carbon dioxide. I also report on how coupled carbon and water fluxes are modulated by biological and ecological factors such as phenology and a suite of structural and functional properties. And, I investigate whether long‐term trends in carbon and water fluxes are emerging in various ecological and climate spaces and the degree to which they may be driven by physical and biological forcings. As a growing number of time series extend up to 20 years in duration, we are at the verge of capturing ecosystem scale trends in the breathing of a changing biosphere. Consequently, flux measurements need to continue to report on future conditions and responses and assess the efficacy of natural climate solutions.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Soil properties and sediment accretion modulate methane fluxes from restored wetlands - Samuel D. Chamberlain; Tyler L. Anthony; Whendee L. Silver; Elke Eichelmann; Kyle S. Hemes; Patricia Y. Oikawa; Cove Sturtevant; Daphne J. Szutu; Joseph G. Verfaillie; Dennis D. Baldocchi (Global Change Biology, 2018)
Wetlands are the largest source of methane ( CH 4 ) globally, yet our understanding of how process‐level controls scale to ecosystem fluxes remains limited. It is particularly uncertain how variable soil properties influence ecosystem CH 4 emissions on annual time scales. We measured ecosystem carbon dioxide ( CO 2 ) and CH 4 fluxes by eddy covariance from two wetlands recently restored on peat and alluvium soils within the Sacramento–San Joaquin Delta of California. Annual CH 4 fluxes from the alluvium wetland were significantly lower than the peat site for multiple years following restoration, but these differences were not explained by variation in dominant climate drivers or productivity across wetlands. Soil iron (Fe) concentrations were significantly higher in alluvium soils, and alluvium CH 4 fluxes were decoupled from plant processes compared with the peat site, as expected when Fe reduction inhibits CH 4 production in the rhizosphere. Soil carbon content and CO 2 uptake rates did not vary across wetlands and, thus, could also be ruled out as drivers of initial CH 4 flux differences. Differences in wetland CH 4 fluxes across soil types were transient; alluvium wetland fluxes were similar to peat wetland fluxes 3 years after restoration. Changing alluvium CH 4 emissions with time could not be explained by an empirical model based on dominant CH 4 flux biophysical drivers, suggesting that other factors, not measured by our eddy covariance towers, were responsible for these changes. Recently accreted alluvium soils were less acidic and contained more reduced Fe compared with the pre‐restoration parent soils, suggesting that CH 4 emissions increased as conditions became more favorable to methanogenesis within wetland sediments. This study suggests that alluvium soil properties, likely Fe content, are capable of inhibiting ecosystem‐scale wetland CH 4 flux, but these effects appear to be transient without continued input of alluvium to wetland sediments.

Evaluation of Density Corrections to Methane Fluxes Measured by Open-Path Eddy Covariance over Contrasting Landscapes - Samuel D. Chamberlain; Joseph Verfaillie; Elke Eichelmann; Kyle S. Hemes; Dennis D. Baldocchi (Boundary-Layer Meteorology, 2017)

Effects of seasonality, transport pathway, and spatial structure on greenhouse gas fluxes in a restored wetland - Gavin McNicol; Cove S. Sturtevant; Sara H. Knox; Iryna Dronova; Dennis D. Baldocchi; Whendee L. Silver (Global Change Biology, 2017)
Wetlands can influence global climate via greenhouse gas ( GHG ) exchange of carbon dioxide ( CO 2 ), methane ( CH 4 ), and nitrous oxide (N 2 O). Few studies have quantified the full GHG budget of wetlands due to the high spatial and temporal variability of fluxes. We report annual open‐water diffusion and ebullition fluxes of CO 2 , CH 4 , and N 2 O from a restored emergent marsh ecosystem. We combined these data with concurrent eddy‐covariance measurements of whole‐ecosystem CO 2 and CH 4 exchange to estimate GHG fluxes and associated radiative forcing effects for the whole wetland, and separately for open‐water and vegetated cover types. Annual open‐water CO 2 , CH 4 , and N 2 O emissions were 915 ± 95 g C‐ CO 2 m −2 yr −1 , 2.9 ± 0.5 g C‐ CH 4 m −2 yr −1 , and 62 ± 17 mg N‐N 2 O m −2 yr −1 , respectively. Diffusion dominated open‐water GHG transport, accounting for >99% of CO 2 and N 2 O emissions, and ~71% of CH 4 emissions. Seasonality was minor for CO 2 emissions, whereas CH 4 and N 2 O fluxes displayed strong and asynchronous seasonal dynamics. Notably, the overall radiative forcing of open‐water fluxes (3.5 ± 0.3 kg CO 2 ‐eq m −2 yr −1 ) exceeded that of vegetated zones (1.4 ± 0.4 kg CO 2 ‐eq m −2 yr −1 ) due to high ecosystem respiration. After scaling results to the entire wetland using object‐based cover classification of remote sensing imagery, net uptake of CO 2 (−1.4 ± 0.6 kt CO 2 ‐eq yr −1 ) did not offset CH 4 emission (3.7 ± 0.03 kt CO 2 ‐eq yr −1 ), producing an overall positive radiative forcing effect of 2.4 ± 0.3 kt CO 2 ‐eq yr −1 . These results demonstrate clear effects of seasonality, spatial structure, and transport pathway on the magnitude and composition of wetland GHG emissions, and the efficacy of multiscale flux measurement to overcome challenges of wetland heterogeneity.

Photosynthetic responses to temperature across leaf–canopy–ecosystem scales: a 15-year study in a Californian oak-grass savanna - Siyan Ma; Jessica L. Osuna; Joseph Verfaillie; Dennis D. Baldocchi (Photosynthesis Research, 2017)

Drought Influences the Accuracy of Simulated Ecosystem Fluxes: A Model-Data Meta-analysis for Mediterranean Oak Woodlands - Rodrigo Vargas; Oliver Sonnentag; Gab Abramowitz; Arnaud Carrara; Jing Ming Chen; Philippe Ciais; Alexandra Correia; Trevor F. Keenan; Hideki Kobayashi; Jean-Marc Ourcival; Dario Papale; David Pearson; et al. (Ecosystems, 2013)

Convergence of potential net ecosystem production among contrasting C 3 grasslands - Matthias Peichl; Oliver Sonnentag; Georg Wohlfahrt; Lawrence B. Flanagan; Dennis D. Baldocchi; Gerard Kiely; Marta Galvagno; Damiano Gianelle; Barbara Marcolla; Casimiro Pio; Mirco Migliavacca; Michael B. Jones; et al. (Ecology Letters, 2013)
Metabolic theory and body size constraints on biomass production and decomposition suggest that differences in the intrinsic potential net ecosystem production ( NEP POT ) should be small among contrasting C 3 grasslands and therefore unable to explain the wide range in the annual apparent net ecosystem production ( NEP APP ) reported by previous studies. We estimated NEP POT for nine C 3 grasslands under contrasting climate and management regimes using multiyear eddy covariance data. NEP POT converged within a narrow range, suggesting little difference in the net carbon dioxide uptake capacity among C 3 grasslands. Our results indicate a unique feature of C 3 grasslands compared with other terrestrial ecosystems and suggest a state of stability in NEP POT due to tightly coupled production and respiration processes. Consequently, the annual NEP APP of C 3 grasslands is primarily a function of seasonal and short‐term environmental and management constraints, and therefore especially susceptible to changes in future climate patterns and associated adaptation of management practices.

A randomization method for efficiently and accurately processing fine roots, and separating them from debris, in the laboratory - Laura E. Koteen; Dennis D. Baldocchi (Plant and Soil, 2013)

TRY – a global database of plant traits - J. KATTGE; S. DÍAZ; S. LAVOREL; I. C. PRENTICE; P. LEADLEY; G. BÖNISCH; E. GARNIER; M. WESTOBY; P. B. REICH; I. J. WRIGHT; J. H. C. CORNELISSEN; C. VIOLLE; et al. (Global Change Biology, 2011)
Plant traits – the morphological, anatomical, physiological, biochemical and phenological characteristics of plants and their organs – determine how primary producers respond to environmental factors, affect other trophic levels, influence ecosystem processes and services and provide a link from species richness to ecosystem functional diversity. Trait data thus represent the raw material for a wide range of research from evolutionary biology, community and functional ecology to biogeography. Here we present the global database initiative named TRY, which has united a wide range of the plant trait research community worldwide and gained an unprecedented buy‐in of trait data: so far 93 trait databases have been contributed. The data repository currently contains almost three million trait entries for 69 000 out of the world's 300 000 plant species, with a focus on 52 groups of traits characterizing the vegetative and regeneration stages of the plant life cycle, including growth, dispersal, establishment and persistence. A first data analysis shows that most plant traits are approximately log‐normally distributed, with widely differing ranges of variation across traits. Most trait variation is between species (interspecific), but significant intraspecific variation is also documented, up to 40% of the overall variation. Plant functional types (PFTs), as commonly used in vegetation models, capture a substantial fraction of the observed variation – but for several traits most variation occurs within PFTs, up to 75% of the overall variation. In the context of vegetation models these traits would better be represented by state variables rather than fixed parameter values. The improved availability of plant trait data in the unified global database is expected to support a paradigm shift from species to trait‐based ecology, offer new opportunities for synthetic plant trait research and enable a more realistic and empirically grounded representation of terrestrial vegetation in Earth system models.

Large Greenhouse Gas Emissions from a Temperate Peatland Pasture - Yit Arn Teh; Whendee L. Silver; Oliver Sonnentag; Matteo Detto; Maggi Kelly; Dennis D. Baldocchi (Ecosystems, 2011)

Multiscale analysis of temporal variability of soil CO 2 production as influenced by weather and vegetation - RODRIGO VARGAS; MATTEO DETTO; DENNIS D. BALDOCCHI; MICHAEL F. ALLEN (Global Change Biology, 2010)
Ecosystem processes are influenced by weather and climatic perturbations at multiple temporal scales with a large range of amplitudes and phases. Technological advances of automated biometeorological measurements provide the opportunity to apply spectral methods on continuous time series to identify differences in amplitudes and phases and relationships with weather variation. Here we used wavelet coherence analysis to study the temporal covariance between soil CO 2 production and soil temperature, soil moisture, and photosynthetically active radiation (PAR). Continuous (hourly average) data were acquired over 2 years among three vegetation types in a semiarid mixed temperate forest. We showed that soil temperature and soil moisture influence soil CO 2 production differently at multiple periods (e.g. hours, days, weeks, months, years), especially after rain pulse events. Our results provide information about the periodicity of soil CO 2 production among vegetation types, and provide insights about processes controlling CO 2 production through the study of phase relationships between two time series (e.g. soil CO 2 production and PAR). We tested the performance of empirical models of soil CO 2 production using the continuous wavelet transform. These models, built around soil temperature and moisture, failed at multiple periods across the measured dates, suggesting that empirical models should include other factors that regulate soil CO 2 production at different temporal scales. Our results add a new dimension for the analysis of continuous time series of biometeorological measurements and model testing, which will prove useful for analysis of increasing sensor data obtained by environmental networks.

Albedo estimates for land surface models and support for a new paradigm based on foliage nitrogen concentration - D. Y. HOLLINGER; S. V. OLLINGER; A. D. RICHARDSON; T. P. MEYERS; D. B. DAIL; M. E. MARTIN; N. A. SCOTT; T. J. ARKEBAUER; D. D. BALDOCCHI; K. L. CLARK; P. S. CURTIS; K. J. DAVIS; et al. (Global Change Biology, 2010)
Vegetation albedo is a critical component of the Earth's climate system, yet efforts to evaluate and improve albedo parameterizations in climate models have lagged relative to other aspects of model development. Here, we calculated growing season albedos for deciduous and evergreen forests, crops, and grasslands based on over 40 site‐years of data from the AmeriFlux network and compared them with estimates presently used in the land surface formulations of a variety of climate models. Generally, the albedo estimates used in land surface models agreed well with this data compilation. However, a variety of models using fixed seasonal estimates of albedo overestimated the growing season albedo of northerly evergreen trees. In contrast, climate models that rely on a common two‐stream albedo submodel provided accurate predictions of boreal needle‐leaf evergreen albedo but overestimated grassland albedos. Inverse analysis showed that parameters of the two‐stream model were highly correlated. Consistent with recent observations based on remotely sensed albedo, the AmeriFlux dataset demonstrated a tight linear relationship between canopy albedo and foliage nitrogen concentration (for forest vegetation: albedo=0.01+0.071%N, r 2 =0.91; forests, grassland, and maize: albedo=0.02+0.067%N, r 2 =0.80). However, this relationship saturated at the higher nitrogen concentrations displayed by soybean foliage. We developed similar relationships between a foliar parameter used in the two‐stream albedo model and foliage nitrogen concentration. These nitrogen‐based relationships can serve as the basis for a new approach to land surface albedo modeling that simplifies albedo estimation while providing a link to other important ecosystem processes.

Latitudinal patterns of magnitude and interannual variability in net ecosystem exchange regulated by biological and environmental variables - WENPING YUAN; YIQI LUO; ANDREW D. RICHARDSON; RAM OREN; SEBASTIAAN LUYSSAERT; IVAN A. JANSSENS; REINHART CEULEMANS; XUHUI ZHOU; THOMAS GRÜNWALD; MARC AUBINET; CHRISTIAN BERHOFER; DENNIS D. BALDOCCHI; et al. (Global Change Biology, 2009)
Over the last two and half decades, strong evidence showed that the terrestrial ecosystems are acting as a net sink for atmospheric carbon. However the spatial and temporal patterns of variation in the sink are not well known. In this study, we examined latitudinal patterns of interannual variability (IAV) in net ecosystem exchange (NEE) of CO 2 based on 163 site‐years of eddy covariance data, from 39 northern‐hemisphere research sites located at latitudes ranging from ∼29°N to ∼64°N. We computed the standard deviation of annual NEE integrals at individual sites to represent absolute interannual variability (AIAV), and the corresponding coefficient of variation as a measure of relative interannual variability (RIAV). Our results showed decreased trends of annual NEE with increasing latitude for both deciduous broadleaf forests and evergreen needleleaf forests. Gross primary production (GPP) explained a significant proportion of the spatial variation of NEE across evergreen needleleaf forests, whereas, across deciduous broadleaf forests, it is ecosystem respiration (Re). In addition, AIAV in GPP and Re increased significantly with latitude in deciduous broadleaf forests, but AIAV in GPP decreased significantly with latitude in evergreen needleleaf forests. Furthermore, RIAV in NEE, GPP, and Re appeared to increase significantly with latitude in deciduous broadleaf forests, but not in evergreen needleleaf forests. Correlation analyses showed air temperature was the primary environmental factor that determined RIAV of NEE in deciduous broadleaf forest across the North American sites, and none of the chosen climatic factors could explain RIAV of NEE in evergreen needleleaf forests. Mean annual NEE significantly increased with latitude in grasslands. Precipitation was dominant environmental factor for the spatial variation of magnitude and IAV in GPP and Re in grasslands.

Intercomparison, interpretation, and assessment of spring phenology in North America estimated from remote sensing for 1982–2006 - MICHAEL A. WHITE; KIRSTEN M. De BEURS; KAMEL DIDAN; DAVID W. INOUYE; ANDREW D. RICHARDSON; OLAF P. JENSEN; JOHN O'KEEFE; GONG ZHANG; RAMAKRISHNA R. NEMANI; WILLEM J. D. Van LEEUWEN; JESSLYN F. BROWN; ALLARD De WIT; et al. (Global Change Biology, 2009)
Shifts in the timing of spring phenology are a central feature of global change research. Long‐term observations of plant phenology have been used to track vegetation responses to climate variability but are often limited to particular species and locations and may not represent synoptic patterns. Satellite remote sensing is instead used for continental to global monitoring. Although numerous methods exist to extract phenological timing, in particular start‐of‐spring (SOS), from time series of reflectance data, a comprehensive intercomparison and interpretation of SOS methods has not been conducted. Here, we assess 10 SOS methods for North America between 1982 and 2006. The techniques include consistent inputs from the 8 km Global Inventory Modeling and Mapping Studies Advanced Very High Resolution Radiometer NDVIg dataset, independent data for snow cover, soil thaw, lake ice dynamics, spring streamflow timing, over 16 000 individual measurements of ground‐based phenology, and two temperature‐driven models of spring phenology. Compared with an ensemble of the 10 SOS methods, we found that individual methods differed in average day‐of‐year estimates by ±60 days and in standard deviation by ±20 days. The ability of the satellite methods to retrieve SOS estimates was highest in northern latitudes and lowest in arid, tropical, and Mediterranean ecoregions. The ordinal rank of SOS methods varied geographically, as did the relationships between SOS estimates and the cryospheric/hydrologic metrics. Compared with ground observations, SOS estimates were more related to the first leaf and first flowers expanding phenological stages. We found no evidence for time trends in spring arrival from ground‐ or model‐based data; using an ensemble estimate from two methods that were more closely related to ground observations than other methods, SOS trends could be detected for only 12% of North America and were divided between trends towards both earlier and later spring.

Microbial soil respiration and its dependency on carbon inputs, soil temperature and moisture - J. CURIEL YUSTE; D. D. BALDOCCHI; A. GERSHENSON; A. GOLDSTEIN; L. MISSON; S. WONG (Global Change Biology, 2007)
This experiment was designed to study three determinant factors in decomposition patterns of soil organic matter (SOM): temperature, water and carbon (C) inputs. The study combined field measurements with soil lab incubations and ends with a modelling framework based on the results obtained. Soil respiration was periodically measured at an oak savanna woodland and a ponderosa pine plantation. Intact soils cores were collected at both ecosystems, including soils with most labile C burnt off, soils with some labile C gone and soils with fresh inputs of labile C. Two treatments, dry‐field condition and field capacity, were applied to an incubation that lasted 111 days. Short‐term temperature changes were applied to the soils periodically to quantify temperature responses. This was done to prevent confounding results associated with different pools of C that would result by exposing treatments chronically to different temperature regimes. This paper discusses the role of the above‐defined environmental factors on the variability of soil C dynamics. At the seasonal scale, temperature and water were, respectively, the main limiting factors controlling soil CO 2 efflux for the ponderosa pine and the oak savanna ecosystems. Spatial and seasonal variations in plant activity (root respiration and exudates production) exerted a strong influence over the seasonal and spatial variation of soil metabolic activity. Mean residence times of bulk SOM were significantly lower at the Nitrogen (N)‐rich deciduous savanna than at the N‐limited evergreen dominated pine ecosystem. At shorter time scales (daily), SOM decomposition was controlled primarily by temperature during wet periods and by the combined effect of water and temperature during dry periods. Secondary control was provided by the presence/absence of plant derived C inputs (exudation). Further analyses of SOM decomposition suggest that factors such as changes in the decomposer community, stress‐induced changes in the metabolic activity of decomposers or SOM stabilization patterns remain unresolved, but should also be considered in future SOM decomposition studies. Observations and confounding factors associated with SOM decomposition patterns and its temperature sensitivity are summarized in the modeling framework.

Reconciling Carbon-cycle Concepts, Terminology, and Methods - F. S. Chapin; G. M. Woodwell; J. T. Randerson; E. B. Rastetter; G. M. Lovett; D. D. Baldocchi; D. A. Clark; M. E. Harmon; D. S. Schimel; R. Valentini; C. Wirth; J. D. Aber; et al. (Ecosystems, 2006)

Tree photosynthesis modulates soil respiration on a diurnal time scale - Jianwu Tang; Dennis D. Baldocchi; Liukang Xu (Global Change Biology, 2005)
To estimate how tree photosynthesis modulates soil respiration, we simultaneously and continuously measured soil respiration and canopy photosynthesis over an oak‐grass savanna during the summer, when the annual grass between trees was dead. Soil respiration measured under a tree crown reflected the sum of rhizosphere respiration and heterotrophic respiration; soil respiration measured in an open area represented heterotrophic respiration. Soil respiration was measured using solid‐state CO 2 sensors buried in soils and the flux‐gradient method. Canopy photosynthesis was obtained from overstory and understory flux measurements using the eddy covariance method. We found that the diurnal pattern of soil respiration in the open was driven by soil temperature, while soil respiration under the tree was decoupled with soil temperature. Although soil moisture controlled the seasonal pattern of soil respiration, it did not influence the diurnal pattern of soil respiration. Soil respiration under the tree controlled by the root component was strongly correlated with tree photosynthesis, but with a time lag of 7–12 h. These results indicate that photosynthesis drives soil respiration in addition to soil temperature and moisture.

Predicting the onset of net carbon uptake by deciduous forests with soil temperature and climate data: a synthesis of FLUXNET data - Dennis D. Baldocchi; T. A. Black; P. S. Curtis; E. Falge; J. D. Fuentes; A. Granier; L. Gu; A. Knohl; K. Pilegaard; H. P. Schmid; R. Valentini; K. Wilson; et al. (International Journal of Biometeorology, 2005)

Assessing the eddy covariance technique for evaluating carbon dioxide exchange rates of ecosystems: past, present and future - DENNIS D. BALDOCCHI (Global Change Biology, 2003)
The eddy covariance technique ascertains the exchange rate of CO 2 across the interface between the atmosphere and a plant canopy by measuring the covariance between fluctuations in vertical wind velocity and CO 2 mixing ratio. Two decades ago, the method was employed to study CO 2 exchange of agricultural crops under ideal conditions during short field campaigns. During the past decade the eddy covariance method has emerged as an important tool for evaluating fluxes of carbon dioxide between terrestrial ecosystems and the atmosphere over the course of a year, and more. At present, the method is being applied in a nearly continuous mode to study carbon dioxide and water vapor exchange at over a hundred and eighty field sites, worldwide. The objective of this review is to assess the eddy covariance method as it is being applied by the global change community on increasingly longer time scales and over less than ideal surfaces. The eddy covariance method is most accurate when the atmospheric conditions (wind, temperature, humidity, CO 2 ) are steady, the underlying vegetation is homogeneous and it is situated on flat terrain for an extended distance upwind. When the eddy covariance method is applied over natural and complex landscapes or during atmospheric conditions that vary with time, the quantification of CO 2 exchange between the biosphere and atmosphere must include measurements of atmospheric storage, flux divergence and advection. Averaging CO 2 flux measurements over long periods (days to year) reduces random sampling error to relatively small values. Unfortunately, data gaps are inevitable when constructing long data records. Data gaps are generally filled with values produced from statistical and empirical models to produce daily and annual sums of CO 2 exchange. Filling data gaps with empirical estimates do not introduce significant bias errors because the empirical algorithms are derived from large statistical populations. On the other hand, flux measurement errors can be biased at night when winds are light and intermittent. Nighttime bias errors tend to produce an underestimate in the measurement of ecosystem respiration. Despite the sources of errors associated with long‐term eddy flux measurements, many investigators are producing defensible estimates of annual carbon exchange. When measurements come from nearly ideal sites the error bound on the net annual exchange of CO 2 is less than ±50 g C m −2 yr −1 . Additional confidence in long‐term measurements is growing because investigators are producing values of net ecosystem productivity that are converging with independent values produced by measuring changes in biomass and soil carbon, as long as the biomass inventory studies are conducted over multiple years.

Correction Of Eddy-Covariance Measurements Incorporating Both Advective Effects And Density Fluxes - Kyaw Tha Paw U; Dennis D. Baldocchi; Tilden P. Meyers; Kell B. Wilson (Boundary-Layer Meteorology, 2000)

Arctic and boreal ecosystems of western North America as components of the climate system - F. S. Chapin; A. D. Mcguire; J. Randerson; R. Pielke; D. Baldocchi; S. E. Hobbie; N. Roulet; W. Eugster; E. Kasischke; E. B. Rastetter; S. A. Zimov; S. W. Running (Global Change Biology, 2000)
Summary Synthesis of results from several Arctic and boreal research programmes provides evidence for the strong role of high‐latitude ecosystems in the climate system. Average surface air temperature has increased 0.3 °C per decade during the twentieth century in the western North American Arctic and boreal forest zones. Precipitation has also increased, but changes in soil moisture are uncertain. Disturbance rates have increased in the boreal forest; for example, there has been a doubling of the area burned in North America in the past 20 years. The disturbance regime in tundra may not have changed. Tundra has a 3–6‐fold higher winter albedo than boreal forest, but summer albedo and energy partitioning differ more strongly among ecosystems within either tundra or boreal forest than between these two biomes. This indicates a need to improve our understanding of vegetation dynamics within, as well as between, biomes. If regional surface warming were to continue, changes in albedo and energy absorption would likely act as a positive feedback to regional warming due to earlier melting of snow and, over the long term, the northward movement of treeline. Surface drying and a change in dominance from mosses to vascular plants would also enhance sensible heat flux and regional warming in tundra. In the boreal forest of western North America, deciduous forests have twice the albedo of conifer forests in both winter and summer, 50–80% higher evapotranspiration, and therefore only 30–50% of the sensible heat flux of conifers in summer. Therefore, a warming‐induced increase in fire frequency that increased the proportion of deciduous forests in the landscape, would act as a negative feedback to regional warming. Changes in thermokarst and the aerial extent of wetlands, lakes, and ponds would alter high‐latitude methane flux. There is currently a wide discrepancy among estimates of the size and direction of CO 2 flux between high‐latitude ecosystems and the atmosphere. These discrepancies relate more strongly to the approach and assumptions for extrapolation than to inconsistencies in the underlying data. Inverse modelling from atmospheric CO 2 concentrations suggests that high latitudes are neutral or net sinks for atmospheric CO 2 , whereas field measurements suggest that high latitudes are neutral or a net CO 2 source. Both approaches rely on assumptions that are difficult to verify. The most parsimonious explanation of the available data is that drying in tundra and disturbance in boreal forest enhance CO 2 efflux. Nevertheless, many areas of both tundra and boreal forests remain net sinks due to regional variation in climate and local variation in topographically determined soil moisture. Improved understanding of the role of high‐latitude ecosystems in the climate system requires a concerted research effort that focuses on geographical variation in the processes controlling land–atmosphere exchange, species composition, and ecosystem structure. Future studies must be conducted over a long enough time‐period to detect and quantify ecosystem feedbacks.

Land–atmosphere energy exchange in Arctic tundra and boreal forest: available data and feedbacks to climate - Werner Eugster; Wayne R Rouse; Roger A. Pielke Sr; Joseph P. Mcfadden; Dennis D Baldocchi; Timothy G. F Kittel; F. Stuart Chapin; Glen E. Liston; Pier Luigi Vidale; Eugene Vaganov; Scott Chambers (Global Change Biology, 2000)
Summary This paper summarizes and analyses available data on the surface energy balance of Arctic tundra and boreal forest. The complex interactions between ecosystems and their surface energy balance are also examined, including climatically induced shifts in ecosystem type that might amplify or reduce the effects of potential climatic change. High latitudes are characterized by large annual changes in solar input. Albedo decreases strongly from winter, when the surface is snow‐covered, to summer, especially in nonforested regions such as Arctic tundra and boreal wetlands. Evapotranspiration ( Q E ) of high‐latitude ecosystems is less than from a freely evaporating surface and decreases late in the season, when soil moisture declines, indicating stomatal control over Q E , particularly in evergreen forests. Evergreen conifer forests have a canopy conductance half that of deciduous forests and consequently lower Q E and higher sensible heat flux ( Q H ). There is a broad overlap in energy partitioning between Arctic and boreal ecosystems, although Arctic ecosystems and light taiga generally have higher ground heat flux because there is less leaf and stem area to shade the ground surface, and the thermal gradient from the surface to permafrost is steeper. Permafrost creates a strong heat sink in summer that reduces surface temperature and therefore heat flux to the atmosphere. Loss of permafrost would therefore amplify climatic warming. If warming caused an increase in productivity and leaf area, or fire caused a shift from evergreen to deciduous forest, this would increase Q E and reduce Q H . Potential future shifts in vegetation would have varying climate feedbacks, with largest effects caused by shifts from boreal conifer to shrubland or deciduous forest (or vice versa) and from Arctic coastal to wet tundra. An increase of logging activity in the boreal forests appears to reduce Q E by roughly 50% with little change in Q H , while the ground heat flux is strongly enhanced.

Measuring and modelling seasonal variation of carbon dioxide and water vapour exchange of a Pinus ponderosa forest subject to soil water deficit - B. E. Law; M. Williams; P. M. Anthoni; D. D. Baldocchi; M. H. Unsworth (Global Change Biology, 2000)
Summary We conducted ecosystem carbon and water vapour exchange studies in an old‐growth Pinus ponderosa forest in the Pacific North‐west region of the United States. The canopy is heterogeneous, with tall multiaged trees and an open, clumped canopy with low leaf area. Carbon assimilation can occur throughout relatively mild winters, although night frosts can temporarily halt the process and physiological factors limit its efficiency. In contrast, carbon assimilation is often limited in the ‘growing season’ by stomatal closure associated with high evaporative demand ( D ) and soil water deficits. All of these factors present a challenge to effectively modelling ecosystem processes. Our objective was to generate an understanding of the controls on ecosystem processes across seasonal and annual cycles from a combination of fine‐scale process modelling, ecophysiological measurements, and carbon and water vapour fluxes measured by the eddy covariance method. Flux measurements showed that 50% and 70% of the annual carbon uptake occurred outside the ‘growing season’ (defined as bud break to senescence, ∼ days 125–275) in 1996 and 1997. On a daily basis in summer, net ecosystem productivity (NEP) was low when D and soil water deficits were large. Whole ecosystem water vapour fluxes (LE) increased from spring to summer (1.0–1.9 mm d−1) as conducting leaf area increased by 30% and as evaporative demand increased, while evaporation from the soil surface became a smaller portion of total LE as soil water deficits increased. The models underestimated soil evaporation, particularly following rain. In the SPA model, varying the temperature optimum for photosynthesis seasonally resulted in overestimation of carbon uptake in winter and spring, showing that in coniferous forests, assumptions about temperature optima are clearly important. Daily estimates of soil surface CO 2 flux from measurements and site meteorological data demonstrated that modelling of soil CO 2 flux based on an Arrhenius‐type equation in CANPOND overestimated CO 2 respired from the soil during drought and when temperatures were low.

Commentary: Carbon Metabolism of the Terrestrial Biosphere: A Multitechnique Approach for Improved Understanding - J. G. Canadell; H. A. Mooney; D. D. Baldocchi; J. A. Berry; J. R. Ehleringer; C. B. Field; S. T. Gower; D. Y. Hollinger; J. E. Hunt; R. B. Jackson; S. W. Running; G. R. Shaver; et al. (Ecosystems, 2000)

The use of relaxed eddy accumulation to measure biosphere-atmosphere exchange of isoprene and other biological trace gases - D. R. Bowling; A. A. Turnipseed; A. C. Delany; D. D. Baldocchi; J. P. Greenberg; R. K. Monson (Oecologia, 1998)